Outcomes in human T-cell leukemia virus type I carriers after hematopoietic stem cell transplantation for diseases other than adult T cell leukemia/lymphoma: a Japanese national surveyResearch in context - Nobuaki Nakano; Hideki Nakasone; Shigeo Fuji; Akihito Shinohara; Ritsuro Suzuki; Atae Utsunomiya; Tetsuya Eto; Satoko Morishima; Kazuhiro Ikegame; Yasutaka Kakinoki; Ken-ichi Matsuoka; Yasuo Mori; et al. (Elsevier, 2023)
Summary: Background: Human T-cell leukemia virus type I (HTLV-1) is a retrovirus known to cause adult T-cell leukemia/lymphoma (ATL). There are few reports on hematopoietic stem cell transplantation (HSCT) for d HTLV-1 carriers with diseases other than ATL. Methods: A total of 25,839 patients (24,399 adults and 1440 children) with pre-transplant HTLV-1 serostatus information recorded in the Japanese National Survey Database who had undergone their first HSCT were analyzed. We investigated the overall survival (OS), transplant-related mortality (TRM), and disease-related mortality (DRM) after HSCT in relation to HTLV-1 serologic status. Findings: Three hundred and forty-eight patients were HTLV-1 antibody carriers. The number of HTLV-1 carriers and noncarriers among adult patients who received allogeneic HSCT (allo-HSCT) or autologous HSCT (auto-HSCT) was 237/15,777 and 95/8920, respectively, and was 16/1424 among pediatric patients who received allo-HSCT. No pediatric HTLV-1 carrier recipients undergoing auto-HSCT were identified. There were no significant differences between HTLV-1 carriers and non-carriers regarding stem cell source, disease risk, or HCT-CI score prior to allo-HSCT. Multivariate analysis of OS (P = 0.020) and TRM (P = 0.017) in adult patients showed that HTLV-1 positive status was a significant prognostic factor. In children, TRM was significantly higher (P = 0.019), but OS was not significantly different. In adult patients who underwent auto-HSCT, HTLV-1 positive status was not a significant prognostic factor. In adult allo-HSCT patients, cytomegalovirus reactivation was significantly more common in HTLV-1 carriers (P = 0.001). Interpretation: HTLV-1 antibody positivity was shown to have a poor prognosis in OS and TRM after allo-HSCT in adult patients and in TRM after allo-HSCT in pediatric patients. Funding: This work was supported in part by the practical research programs of the Japan Agency for Medical Research and Development (AMED) under grant number 17ck0106342h0001.